(untitled) (REMUNOM, 2025)
Playful activities, which include games and play in the school environment, are of great importance for children and adolescents with Autism Spectrum Disorder (ASD), as they foster the development of various cognitive skills and promote engagement in social, emotional, and motor aspects. Play is recognized as a highly effective therapeutic resource which, when aligned with the occupational therapist’s care goals, offers innovative responses to meeting the needs of these students and their families. This enables an inclusive approach with meaningful and impactful contributions. Objective: To describe teachers’ perceptions regarding the inclusion of these students. Method: Exploratory, observational, and descriptive research with a qualitative approach, using Bardin’s content analysis. Data collection took place in the municipalities of São Gonçalo, Magé, and Cachoeiras de Macacu, where interviews were conducted with teachers based on the following guiding questions: What are the challenges and possibilities in educating students with ASD? What problems and interventions impact the development of these students’ skills and potential? How do you perceive the role of the occupational therapist in education? Results: The study included 12 participants: 5 general education teachers, 2 special education teachers, 1 school manager, 1 occupational therapist, and 3 scholarship students. From the participants’ responses, three categories emerged: Challenges in Communication and Social Interaction, Lack of Ongoing Training and Qualified Professionals, and Teacher Overload and Lack of Structured Support. Conclusion: The occupational therapist can work directly within the school environment, enhancing the occupational performance of students with ASD through the adaptation of educational materials, the use of assistive technologies, support for cognitive development, stimulation of body awareness, and the promotion of play and collective experiences.